JRS Express - Billones,Jayson Carl Coronel,Ronaliza Natanauan,Roschelle Paras, Luis Yves Soyanco,Alvin Tolentino, Jerson and Trinidad, Ivan Anthony. 4 0 16; 5 (2012)
u
Strategic Marketing Plan: (BSBA major in Marketing) - Pamantasan ng Lungsod ng Maynila 2012.
Keywords: 2 -- 0; 6; 20; 20; 2